Children and adults varicocele: diagnostic issues and therapeutical strategies - Valentino, Massimo (Springer International Publishing, 2014)
Varicocele is defined as abnormally dilated scrotal veins. It is present in 15 % of normal males and in 40 % of males with infertility. This disorder is a challenge for the physicians involved in the diagnosis and treatment, as the pathophysiology of varicocele is not yet completely understood. For this reason, accurate diagnostic criteria and clear indications for treatment in asymptomatic adolescents or adults with clinical or subclinical varicocele are still not defined. Ultrasonography (US) is considered the best method for calculating the volume of the testicles, measuring vein diameter and monitoring the growth of the testis in adolescent patients. Color-Doppler US is the method of choice for detecting spermatic vein reflux and for classifying the grade of varicocele. Various classification systems have been published with recommendations on how to perform US imaging of the scrotum. Currently, color-Doppler US and spectral analysis are the most effective, non-invasive diagnostic procedures as they allow detection of subclinical varicocele associated with infertility. Various techniques are used in the treatment of varicocele including open surgery, laparoscopic procedures and interventional radiology. However, there is no consensus among physicians on which technique is the most effective in terms of outcome and complication rates. This review shows that color-Doppler US is currently the most widely employed diagnostic method for detection and classification of varicocele caused by venous reflux, as it is reliable and easily performed. The review also highlights the role of varicocelectomy in the management of adult male infertility.